2018
DOI: 10.1186/s11689-018-9246-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional prosodic change detection in autism Spectrum disorder: an electrophysiological investigation in children and adults

Abstract: BackgroundAutism spectrum disorder (ASD) is characterized by atypical behaviors in social environments and in reaction to changing events. While this dyad of symptoms is at the core of the pathology along with atypical sensory behaviors, most studies have investigated only one dimension. A focus on the sameness dimension has shown that intolerance to change is related to an atypical pre-attentional detection of irregularity. In the present study, we addressed the same process in response to emotional change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 75 publications
2
24
0
1
Order By: Relevance
“…Such atypical change detection in participants with ASD has also been shown in the auditory modality in response to both physical (tone frequency) 10,11 and prosodic (emotional) deviancies 56 . Altogether, results from visual and auditory MMN studies support the hypothesis of a broad impairment of the automatic change detection system.…”
Section: Discussionmentioning
confidence: 75%
“…Such atypical change detection in participants with ASD has also been shown in the auditory modality in response to both physical (tone frequency) 10,11 and prosodic (emotional) deviancies 56 . Altogether, results from visual and auditory MMN studies support the hypothesis of a broad impairment of the automatic change detection system.…”
Section: Discussionmentioning
confidence: 75%
“…Pei et al 3 found in the ASD group a selective amplitude reduction over the right hemisphere to steady-state VEPs pattern reversal. Abnormal hemispheric responses or lack of lateralization have also been described in the auditory domain 4143 , suggesting that this effect is not visual-specific, but could be a core feature of ASD. A smaller activity to faces is often reported in the right hemisphere 44,45 ; this hypo-activation is often discussed as an atypical social processing.…”
Section: Discussionmentioning
confidence: 99%
“…Using electroencephalography (EEG), it was shown that children with ASD, including both children with normal intelligence and intellectual delay, presented an atypical response to environmental sounds but not to vocal sounds (Bidet-Caulet et al, 2017). Yet, in another study, an atypical response to vocal sounds was observed in children with ASD but not in adults with ASD (Charpentier et al, 2018). It should be noted that only vocal sounds were presented in that later study.…”
Section: Introductionmentioning
confidence: 94%